Penyuluhan Tentang Pengiklanan Dan Pengemasan Produk Kewirausahaan Dalam Rangka Pencegahan Stunting - Annisa Maulidia Rahayyu; Alvin Pratama; Robiatul Muztaba; Tefur Nur Rohman (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Stunting is a serious health problem that has a long-term impact on the quality of human resources, especially in rural areas. This community service aims to increase the understanding of PKK and Posyandu cadres about stunting prevention through advertising and packaging education about simple nutritious food processing made from local ingredients. The method used is interactive socialization. This activity was carried out on December 18, 2024 in Bumisari Village, Natar District, South Lampung Regency. The results of the activity showed an increase in participants' understanding of advertising and packaging. The cadres are committed to disseminating this information to the wider community. Continuous assistance is expected to make Bumisari Village a pilot for simple nutritious food processing products made from local ingredients with attractive packaging.